Entrepreneur personality and gender - Yurrebaso Macho, Amaia; Rodríguez-Parets Carabaza, Carolina; Jáñez González, Álvaro; Picado Valverde, Eva María; Guzmán Ordaz, Raquel; Pérez Iglesias, José Luis (Cuadernos de Relaciones Laborales, 2020)
In the last decade, studies related to entrepreneurial activity, especially those tackling the impact of gender differences on entrepreneurial intention, have gained special importance in scientific literature. In this line of research, the present study focuses on the so-called psychosocial profile of the entrepreneur and its influence on entrepreneurial intention. A sample of 479 entrepreneurs is analyzed, to check if there are gender based psychosocial profiles differences among established businesspeople, as well as the potential influence that these differences may have had on entrepreneurial endurance. Previous scientific evidence supports the existence of gender based differences before trying a business, and it is often assumed that these differences have an impact on intention. However, the results obtained in the present study confirm that these gender based psychosocial differences seem to subside once the business is set. It is concluded that social constructs are possible factors deterring women entrepreneurial initiative, specifically at social images that render women as less able to undertake business initiatives.
Keywords: entrepreneurship; gender; psychosocial profile; entrepreneurial intention